Behavior of High Strength Hybrid Reinforcement Concrete Beams - Al-Billbassi, Khanda Ali; Al-Shamaa , Mushriq Fuad Kadhim (International Journal of Integrated Engineering, 2020)
Six proposed simply supported high strength-steel fiber reinforced concrete (HS-SFRC) beams reinforced with FRP (fiber reinforced polymer) rebars were numerically tested by finite element method using ABAQUS software to investigate their behavior under the flexural failure. The beams were divided into two groups depending on their cross sectional shape. Group A consisted of four trapezoidal beams with dimensions of (height 200 mm, top width 250 mm, and bottom width 125 mm), while group B consisted of two rectangular beams with dimensions of (125 ×200) mm. All specimens have same total length of 1500 mm, and they were also considered to be made of same high strength concrete designed material with 1% volume fraction of steel fiber. Different types and ratios of FRP rebar were used to reinforce these test beams. The study’s principle variables were the amount and type of flexural reinforcement (glass FRP and basalt FRP) and beam cross-sectional shape (rectangular and trapezoidal). The load-deflection behavior and ultimate load capacity of the beams were studied and compared with one another under flexural test with symmetrical two-point loading. The results show that increasing the reinforcement ratio resulted in higher post cracking flexural stiffness, and higher residual strength, as well as caused an increase in the first cracking load and ultimate load capacity ranged from 3 to 16.9%, and 4.6 to 7.3% respectively. When the GFRP rebars replaced by BFRP, the overall beams flexural performance showed outstanding improvements. Moreover the results indicate that increasing the top width of the beam cross section led to a significant enhancement in the first crack load ranged from 16 to 32.4%, also a remarkable increases in the ultimate load capacity in the range of 35.5 to 35.8% were indicated in the trapezoidal beams compared to rectangular beams. However the results show that the deflections were similar and were approximately 1.07–1.54 mm for all test beams. It is worth noting that the general flexural behavior of all the test beams indicated a ductile behavior with a gradual reduction in strength and high residual strength pre to failure due to proposing steel fiber presence.